2006
DOI: 10.1074/jbc.m603678200
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent Modulation of Poly(ADP-ribose) Polymerase-1 Alters Cellular Metabolism and DNA Repair

Abstract: Alterations in the initiation and regulation of caspase-mediated apoptosis are associated with an array of pathological disease states, including chemotherapy resistance in cancer (1). Therefore, elucidating mechanisms that initiate non-caspasemediated cell death are crucial for the development and use of novel anticancer agents.A growing number of chemotherapeutic approaches focus on targeting specific DNA repair enzymes. In particular, inhibitors of poly(ADP-ribose) polymerase-1 (PARP-1) 2 that sensitize cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
182
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(198 citation statements)
references
References 51 publications
16
182
0
Order By: Relevance
“…NAD(P)H quinone oxidoreductase 1 (NQO1) catalyzes the reduction of β-lap to an unstable hydroquinone, which then undergoes rapid oxidization and is reconverted to a stable quinone (14). This repeated oxidation-reduction cycle induces ROS, partially contributing to the tumor killing activity of β-lap (14,15,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAD(P)H quinone oxidoreductase 1 (NQO1) catalyzes the reduction of β-lap to an unstable hydroquinone, which then undergoes rapid oxidization and is reconverted to a stable quinone (14). This repeated oxidation-reduction cycle induces ROS, partially contributing to the tumor killing activity of β-lap (14,15,18).…”
Section: Introductionmentioning
confidence: 99%
“…NAD(P)H quinone oxidoreductase 1 (NQO1) catalyzes the reduction of β-lap to an unstable hydroquinone, which then undergoes rapid oxidization and is reconverted to a stable quinone (14). This repeated oxidation-reduction cycle induces ROS, partially contributing to the tumor killing activity of β-lap (14,15,18).Under physiological conditions, the intracellular level of ROS is tightly regulated by NF-E2 related factor 2 (NFE2L2, also known as NRF2) and its inhibitor protein, Kelch-like ECH-associated protein 1 (KEAP1), which mediates NRF2 degradation. NRF2 is a transcription factor that forms a heterodimer with one of the small Maf-family proteins and binds to an antioxidant-responsive element to activate transcription of target genes, including NQO1 (19,20).…”
mentioning
confidence: 99%
“…66,67 β-lapachone was shown to indirectly inhibit DNA repair enzymes through the modification of the redox homeostasis of the intracellular environment, causing oxidative damage to the cysteine residues of the enzymes and subsequently impairing their structure and function to render them incapable of mediating DNA damage repair. 68,69 Additionally, Neder et al 70 and Oliveira-Brett et al 71 reported that the cytotoxic actions of β-lapachone and related naphthoquinones derive, in part, from the alkylation of exposed thiol or cysteine residues on topoisomerase II. Ortho-quinones such as β-lapachone have better redox cycling ability than para-quinones such as α-lapachone.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it was suggested that the cytotoxic actions of naphthoquinones derive, at least in part, from the alkylation of exposed thiol residues on topoisomerase II-DNA complexes. 70 Because β-lapachone was found to inactivate DNA repair 56,65,69 and because the chemical structures of the tested compounds and β-lapachone are very similar, the potential influence of the studied naphthoquinones on the functionality of DNA repair mechanisms in HL-60 cells was tested by introducing MMS-induced DNA lesions prior to exposure to the tested compounds. MMS is an alkylating agent that directly alkylates the nitrogen of DNA bases.…”
Section: Resultsmentioning
confidence: 99%
“…The anti-tumor activity and the radiosensitizing activity of β-lap are dependent on the cytosolic flavoenzyme NAD(P)H:quinone oxidoreductase (NQO1, E>C>1.6.99.2), which catalyzes the two-electron reduction of endogenous as well as exogenous quinone compounds to their corresponding hydroquinone forms using H + from NADH or NADPH (Boothman et al, 1993;Trush et al, 1996;Pink et al, 2000;Planchon et al, 2001;Tagliarino et al, 2001;Park et al, 2005aPark et al, , 2005bSuzuki et al, 2006;Bey et al, 2007;Choi et al, 2007;Song et al, 2008). Boothman and his colleagues (Trush et al, 1996;Pink et al, 2000;Planchon et al, 2001;Tagliarino et al, 2001;Park et al, 2005b;Bentle et al, 2006;Bey et al, 2007) proposed that NQO1 mediates the two-electron reduction of β-lap and that the reduced form of β-lap is unstable and thus immediately oxidized to the original oxidized form. The intermediate one-electron reduced form of β-lap generates redox reactions creating cytotoxic oxygen species (ROS) leading to apoptosis.…”
Section: Introductionmentioning
confidence: 99%